Assessment of Personality Traits and Their Changes Over the Undergraduate Medical Course: A Pseudo-longitudinal Analysis among Indian Medical Students - Alapan Bandyopadhyay; Arup Jyoti Rout; Mabel Das; Debajyoti Das (University Library System, University of Pittsburgh, 2022)
Background: Personality of medical students have been shown to affect both their academic performance as well as their capabilities to develop rapport with patients, with evidence that they change through the medical course. This research aimed to explore the personality traits of undergraduate medical students and assess whether personality parameters changed throughout the medical education course. Methods: A pseudo-longitudinal design was utilized for this study. A total of 346 MBBS students studying in a Medical College of Eastern India were recruited at different stages of their coursework. These participants were similar in their sociodemographic makeup and differed only with respect to their year of MBBS study. The personality characteristics were assessed among these participants using the short-form revised Eysenck personality inventory. Results: The minimum possible score for each subscale was 0, and the maximum was 12. Mean scores of the participants for the extraversion, neuroticism, psychoticism, and lie scales were 6.17±3.09, 7.51±3.16, 3.40±1.61, and 4.98±2.48, respectively. Females scored significantly higher in neuroticism and lie dimensions. There were significant differences of psychoticism scores between rural and urban background participants. Significant negative trend was seen from the first to the final year of study in the extraversion dimension (Kendall's tau =-0.094, p-value=0.025). Conclusion: Medical students in India scored high on the neuroticism and low on the psychoticism scales of personality with a trend of increasing extraversion over the years of their coursework.